A head teacher’s leadership behaviour when developing the leadership capacity of a school - Sigurðardóttir, Sigríður Margrét; Sigþórsson, Rúnar (Icelandic Journal of Education, 2015)
This article is based on findings drawn from a qualitative case study of a compulsory school in Iceland, where the aim was to investigate how the leadership behaviour of the head teacher had made an impact on the development of the leadership capacity of the school. The leadership behaviour of the head teacher was analysed according to a conceptual framework developed by Lambert (2006). Lambert’s framework is divided into three phases, where the leadership behaviour of the head teacher is described as instructive, transitional and high leadership capacity, depending on where the school is situated on its way from low to high capacity. Within each level, the leadership behaviour of the head teacher is evaluated according to his personal attributes, how he works with school members; and how he uses formal authority. The leadership capacity of a school is seen as an organizational-wide skilful engagement in the field of leadership. A clear connection is made between the leadership capacity of the school and the school’s improvement, since the former is regarded as a necessary condition for sustainable school improvement. The head teacher is seen as a key factor in building the leadership capacity of a school and sustaining school improvement. It has been found that head teachers who succeed in school improvement have certain characteristics, abilities and behaviours in common that others lack or have to a lesser degree (Lambert, 2006). A school was chosen for the study that had the reputation for having made a positive shift in its culture and educational goals, and where the same head teacher had been leading the school from the beginning of this shift to the time of the research. To collect data for the case, thirty visits were made to the school in the school year of 2008–2009. The data comprised observations, examination of documents, semistructured interviews, informal conversations with staff, focus group interviews with students and support staff and a survey sent to parents. Data was analysed as the study ...